Women As Commodities In Two Selected Novels Of Thomas Hardy - Nikandam, Roya (2009)

(untitled)
This research examines the Lacanian psychoanalysis principles underlying selected Hardy’s novels, Tess of the d’Urbervilles and The Mayor of the Casterbridge, and underscores the hypotheses of psychoanalytic feminists such as Julia Kristeva and Luce Irigaray who based their theories on Jacques Lacan’s signification of the symbolic order. The study applies Lacanian concepts as adapted by Kristeva and Irigaray to illustrate men’s control over women and women’s resistance to men’s intention to objectify them. The main theme adopted to study Hardy’s novels is the Unconscious of the Patriarchy in the Victorian Imagination. It is divided into two sections: Lacan and Feminist Psychoanalysts. The discussion will highlight women faced the threat of inferiority and it explains the symbolic world of Lacan attempts to turn women into commodities.Women’s power to destabilize the structures of this particular society will also be expounded by referring to the works of Julia Kristeva and Luce Irigaray. It will be explained that through the connection women have with semiotic language, maternity, abjection/death, and mimesis women are able to threaten the symbolic law. By investigating these theoretical observations, I hope to highlight the continuing issue of commodifying the value and dignity of women which can be observed in the patriarchal system of the Victorian era. The study specifically analyses the reactions of male characters in the novels towards the identity of female protagonists which lead to the conclusion that a woman’s self is worthless, valueless and is totally rejected in the symbolic law. In the light of feminist’s psychoanalytic concepts, the study finds the female capability to threaten the unconscious of her identity in the Victorian symbolic era.